First Identification of Culex flavivirus (Flaviviridae) in Brazil - Machado, Daiane Cristina [UNESP]; Mondini, Adriano [UNESP]; Santana, Vinicius dos Santos [UNESP]; Kamiya Yonamine, Patricia Tiemi [UNESP]; Chiaravalloti Neto, Francisco; de Andrade Zanotto, Paolo Marinho; Nogueira, Mauricio Lacerda (Karger, 2012)
Introduction: Culex flavivirus (CxFV) was first isolated in 2007 from Culex pipiens in Japan and then identified in several other countries. Characterization of the CxFV showed that all strains are related to the cell fusing agent virus. In this manuscript we report the first identification of CxFV in South America. Material and Methods: We have collected Culex sp. mosquitoes using BG-Sentinel traps and manual aspirators. They were pooled according to genus, species, sex and location. Viral RNA was extracted and multiplex nested PCR was performed to test the presence of Flavivirus. The positive samples were isolated in C6/36 cells and sequenced for phylogenetic analyses. Results: 265 female Culex mosquitoes pooled in 83 pools were tested with specific CxFV, Saint Louis encephalitis virus (SLEV) and West Nile virus (WNV) primers. Our sequence data indicated maximum sequence similarity of 97% with CxFV. Discussion: In this study we report the circulation of CxFV in an urban setting where SLEV had previously caused an outbreak. In terms of public health, this is an important finding due to the assumption that the previous exposition of mosquitoes to CxFV might lessen the susceptibility of these mosquitoes to other flaviviruses. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Culex flavivirus; West Nile virus; Phylogenetic analysis